EFFECTS OF TEMPERATURE, SALINITY AND FEED ON THE SURVIVAL AND GROWTH OF JUVENILE SEA CUCUMBER, Bohadschia marmorata - MJ Chu Yuan Kee; Chandani Appadoo (JOURNAL OF COASTAL DEVELOPMENT, 2007)
The survival and growth of tropical sea cucumber, Bohadschia marmorata (Jaeger) was investigated Juvenile B, marmorata were collected in the wild from La Prairie, in the south west coast of Mauritius and was reared at Albion Fisheries Research Centre (AF RC). The sea cucumbers were stacked at a density of six individuals per tank in three separate experiments: temperature (26, 28 and 32”C), salinity (25, 30 and 36%a) and feed (macro algal paste and a mixture of macro algal paste supplemented with /5% powdered fish fee¢0. During temperature and salinity treatments, B. marmorata were fed with a macro algal paste anlv. Temperature and salinity treatments were monitored for 63 days and ked experiment for 35 days. B. marmorata showed a negative growth in all salinity and temperature treatments. Survival of B. marmorata was 9l.67 and 66.65% in temperature 28 and 32”C, respective. All B. marmorata survived at temperature 26 DC and had a specyic growth rate of ~0. 78% day". The specyic growth rate of B. marmorata at temperature 28"C and 32"C was —I. 03% day" and -/,23% day" respectivelv. B. marmorata displayed /00% survival rate at salinities 25 and 36%.;. and 9/.67% at salinity 30964; Specific growth rates of B. marmorata showed a descending trend in the order of salinity 25%.1 (·/.07% day") >30%a (-/.05 % day`,) >36%a (-0. 78 % day`!). Better growth was obtained when B. marmorata were fed with a mixture of algae and fish feed (0.3/% day"), as compared with ajeed containing pure algal paste only (-l.34%day"}. This study provides some indications on the rearing conditions for B. marmorata, but more studies are needed for rnariculture purposes.